Synthesis of Nitrogen-Doped ZnS with Camellia Brushfield Yellow Nanostructures for Enhanced Photocatalytic Activity under Visible Light Irradiation - Gang-Juan Lee; Chi-Lun Hong; Valentina Batalova; Gennady Mokrousov; Jerry Wu (International Journal of Photoenergy)
Nitrogen modified zinc sulfide photocatalysts were successfully prepared and characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), high-resolution transmission electron microscopy (HR-TEM), X-ray photoelectron spectroscopy (XPS), and surface area analysis. Thermal decomposition of the semisolid was carried out under nitrogen conditions at 500°C for 2 hours, and a series of nitrogen-doped ZnS photocatalysts were produced by controlling inflow flow rate of nitrogen at 15–140 mL/min. Optical characterizations of the synthesized N-doping ZnS substantially show the shifted photoabsorption properties from ultraviolet (UV) region to visible light. The band gaps of nitrogen-doped ZnS composite catalysts were calculated to be in the range of 2.58~2.74 eV from the absorptions edge position. The 15N/ZnS catalyst shows the highest photocatalytic activity, which results in 75.7% degradation of Orange II dye in 5 hrs by visible light irradiation, compared with pristine ZnS and higher percentage N-doping ZnS photocatalysts.